Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/we.1962
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence influence on wind energy extraction for a medium size vertical axis wind turbine

Abstract: The relation between power performance and turbulence intensity for a VAWT H-rotor is studied using logged data from a 14 month (discontinuous) period with the H-rotor operating in wind speeds up to 9 m/s. The turbine, designed originally for a nominal power of 200 kW, operated during this period mostly in a restricted mode due to mechanical concerns, reaching power levels up to about 80 kW. Two different approaches are used for presenting results, one that can be compared to power curves consistent with the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 20 publications
2
31
1
Order By: Relevance
“…In the case of the VAWT, a minor influence of the surface condition in the obtained C P is noticed. Similar results were obtained in the experimental work of Möllerström et al, which showed a slightly higher efficiency of a VAWT at higher turbulence, proposing that the H‐rotor is appropriate for wind sites with turbulent winds.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the VAWT, a minor influence of the surface condition in the obtained C P is noticed. Similar results were obtained in the experimental work of Möllerström et al, which showed a slightly higher efficiency of a VAWT at higher turbulence, proposing that the H‐rotor is appropriate for wind sites with turbulent winds.…”
Section: Resultsmentioning
confidence: 99%
“…Only one 200 kW turbine was ever built by vertical wind AB, making the T1-turbine unique. The turbine, which is located at Thorsholm (56°56ʹ29ʺN, 12°30ʹ38ʺE) just outside of Falkenberg at the west coast of Sweden, is today owned by Uppsala University and it is the subject of research in a variety of fields [20][21][22][23]. The T1-turbine has a direct drive permanent magnet synchronous generator mounted at the bottom of the tower and connected to the rotor by a steel shaft.…”
Section: Wind Turbine Systemmentioning
confidence: 99%
“…For the full-Darrieus turbine, the blade works in the stall region for parts of the cross-section area, decreasing the contribution from these parts. Since the power coefficient of the T1 turbine is measured to peak at about C p ¼0.33 [41], we may assume a power-coefficient loss of Δ = C 0.07 p due to the presence of the struts. The corresponding power loss at hub-height wind speed u ¼6 m/s amounts to: …”
Section: Noise Prediction Using the Inflow-turbulence Modelmentioning
confidence: 99%